Konsep dasar dan teori sastra Indonesia - Mardhiyah, Ifatul (Maliki Interdisciplinary Journal, 2024)
Literature is a work expressed by someone and arranged in such a way as to produce a beautiful work of art. The work of art can be interpreted as a literary work if a person or reader is able to know, absorb, and understand the meaning of the literature. Therefore, even though we are just connoisseurs of literature, we are also able to understand its meaning through literary theory. Because basically literary works are able to give us an art of life and are very useful for us and can give readers awareness about what life really means. It's not just life that can be illustrated in fictional form. Sometimes the artist is also able to illustrate the work through his story, his love, his opinion and also his experience. However, there are some scientists who reveal that not all texts can be interpreted as literary works. This can be interpreted as a literary work if it contains aesthetic value, which means that readers are able to benefit from a work that is read, able to move their creativity and provide beauty and enjoyment through aesthetic elements.